Tamaricion dalmaticae, a new alliance from the eastern Adriatic - Jasprica, Nenad (Hacquetia, 2016)
The paper describes the Tamaricion dalmaticae alliance and the Tamaricetum dalmaticae association, a new syntaxa localized under the saline or sub-halophilous conditions within the thermo-mediterranean and meso-mediterranean belts of the eastern Adriatic coast. The Tamaricion dalmaticae alliance is considered analogous to the Western Mediterranean Tamaricion africanae. The Tamaricetum dalmaticae association shows the high ecological amplitude of in terms of moisture. It develops on sandy soils only periodically inundated with sea or brackish waters, as well as on non-flooded areas in south Croatia, Montenegro and NW Albania. In Croatia, Tamaricetum dalmaticae has connections with the halophyte communities of the Sarcocornietea fruticosae and Ammophiletea classes, and the xerophilous ruderal communities of the Artemisietea vulgaris class. The habitats are exposed to disturbances and fragmentation.